2014
DOI: 10.1039/c3tc32430c
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the efficiency of opto-electronic devices by the cathode modification

Abstract: A poly(vinyl alcohol) is applied to organic optoelectronic devices as a cathode buffer layer to improve the performances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 55 publications
1
16
0
Order By: Relevance
“…Here, we found that the V oc data of either iPSC or cPSC were not sensitive to the insertion of interlayer. Similar features were observed in the previous research . From the results, electrostatic self‐assembly of PVPy could be potential material as an IFL at the cathode interface in either iPSC or cPSC.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Here, we found that the V oc data of either iPSC or cPSC were not sensitive to the insertion of interlayer. Similar features were observed in the previous research . From the results, electrostatic self‐assembly of PVPy could be potential material as an IFL at the cathode interface in either iPSC or cPSC.…”
Section: Resultssupporting
confidence: 88%
“…For the cathode interface, π‐conjugated oligo‐ or polymer electrolytes have been mainly used for cathode buffer layer to achieve high performance devices. Zwitterionic conjugated polymer electrolytes and nonconjugated polar polymers such as poly(4‐vinylpyrirolidone), poly(4‐vinylalcohol), poly(sodium 4‐styrenesulfonate), polyviologen,, and tetra‐ n ‐alkyl ammonium bromides have been applied to PSCs as an interfacial layer (IFL) at the cathode side to improve the efficiency. By the insertion of the thin film of these materials between the cathode interfaces, the efficiency of the device is improved relative to that of the devices lacking these materials.…”
Section: Introductionmentioning
confidence: 99%
“…9 Those above-mentioned nonconjugated polymers including PEO, PEI, and PEIE are all used as cathode interlayers, because of the possible lone pair electrons or dipole effects. Additionally, some nonconjugated polymers with polar side groups were also used in OSCs as modifiers, such as poly(vinyl alcohol) (PVA) 144 and poly(2,2,6,6-tetramethylpiperidinyloxy methacrylate (PTMA). 145 PVA was used as the cathode interlayer to reduce the Schottky barrier in the device and improve the properties of film, while the PTMA interlayer was used to modify the anode of the device to improve the stability.…”
Section: Acs Applied Materials and Interfacesmentioning
confidence: 99%
“…Reducing the energy gap at the interface and passivation of ZnO surface are important to improve the performances of the devices. Many approaches have been tried to modify the surface of ZnO such as deposition of thin layer of conjugated or non‐conjugated polyelectrolytes (i.e., interlayer), metal chelates, and self‐assembled monolayer (SAM) treatments on the top of the ZnO surface to improve electron collection at the ZnO surface. In case of the former method, the performance of the device is very sensitive to the thickness of the interlayer, which is normally in the range of 5–10 nm and should be optimized.…”
Section: Introductionmentioning
confidence: 99%